Consequências do confinamento de neutrinos na formação de proto-estrelas de neutrons híbridas. - Suely Epztein Grynberg (2000)
We consider a schematic semi-analytical model for the dynamical calculation of collapse-explosion leading to the formation and composition of protoneutron stars. Hadron to quark phase transition is included in a scenario where neutrinos are trapped and interactions among hadrons as well as among quarks are taken into account. The main appeal of the model, besides its simplicity, is that it gives a quantitatively accurate description of all global features of the process such as ejected mass, the energy of the nascent shock wave, the mass and radius of the remnant core. We present the time evolution of the system during the collapse-explosion process and we conclude that the formation of a hybrid remnant core is inhibited by neutrino trapping at the onset of the core bounce.